Persepsi Perawat Berdasarkan Health Belief Model terhadap Kewaspadaan Standar di Rumah Sakit X - Halimatussadiah12, Nanda; Yulis, Rahma; Kartanti, Natalia Ida (Program Studi Keperawatan Universitas Jambi, 2026)
Background: The implementation of standard precautions is essential in preventing infection transmission in hospitals. Nurses, as healthcare workers who have direct contact with patients, are at high risk of exposure to blood and body fluids; therefore, their perceptions play an important role in infection prevention practices. The Health Belief Model (HBM) can be used to explain health-related behaviors based on perceived threats, benefits, and barriers. This study aimed to describe nurses’ perceptions of standard precautions at Hospital X based on the Health Belief Model. Methods: A descriptive quantitative design with a cross-sectional approach was used, involving 317 nurses selected through total sampling. Data were collected using the Indonesian version of the Basic Principles of Standard Precautions questionnaire, which measures perceived threat, perceived benefits, and perceived barriers. Results: The results showed that most nurses had good perceptions, including perceived threat (71.3%), perceived benefits (66.6%), and perceived barriers (64.0%). Most respondents had experienced occupational exposure to blood or body fluids (70.3%) and needle stick injuries (39.7%). The highest incidence of exposure to blood or body fluids was found in the surgical ward (IBS), with 21 respondents (9.4%), and similarly, the highest incidence of needle stick injuries or injuries from infectious sharp objects was also found in the surgical ward, with 21 respondents (16.7%). Conclusion: Nurses’ perceptions of standard precautions were generally good; however, some nurses still had poor perceptions, particularly regarding barriers. These findings highlight the need to strengthen training and improve occupational safety culture to support consistent implementation of standard precautions. Keywords: health belief model; infection prevention; nurse perception; occupational exposure; standard precautions